(untitled) (Journal of the Bangladesh Agricultural University, 2017)
A weed survey was conducted in Agronomy Field Laboratory, BAUFarm and farmers’ fields of Sutiakhali Natunchar village in Mymensingh district during the period from December 2015 to March 2016 to study the weed vegetation in wheat and boro rice. Ten fields were selected for each crop from each location. A quadrat of 0.25 m2 was placed randomly at four places in each plot and the weeds within the quadrat were identified and counted species-wise. The results revealed that the composition of weed species in two different crops was different and the composition of weed flora in each crop under different locations was also different. In wheat, a total number of 29 weed species belonging to 16 families were found from all three locations. The infesting weed species were 18 in Agronomy Field Laboratory, 16 species in BAU Farm and 19 species in farmers’ fields. From the five most dominant species, Polygonum hydropiper had the highest relative abundance value in both Agronomy Field Laboratory and BAU Farm and on the other hand, in farmers’ field, a new weed species, Eleusine indica was in the top most of the dominant list. The other weed species which were present in the dominant list of three locations were Cynodon dactylon, Cyperus rotundus, Paspalum distichum, Chenopodium album, Marsilea quadrifolia and Leucas aspera. In boro rice fields, among the three locations, 25 weed species were observed in total belonging to 13 families. Of which, 20 weed species were found in both Agronomy Field Laboratory and BAU Farm whereas in farmers’ fields, 21 weed species were identified. In both Agronomy Field Laboratory and BAU Farm, Eleocharis atropurpurea had the highest abundance value but in farmers’ field, Cyperus difformis occupied the highest value. The other dominant weed species were Leersia hexandra, Monochoria vaginalis, Echinochloa crusgalli, Paspalum distichum and Alternanthera philoxeroides found in three locations. Many common weeds were present in three locations in a crop but their frequency, uniformity, density and relative abundance value were different. The similarity index of weed species between wheat and boro rice indicated that the infesting weed species between the two crops was less associated. Thus the weed divergence in boro rice with wheat was high. From this study it was clear that the weed infestation was changed by crop and locations. In this study a little bit divergence and ranking of five most abundant weed species and low similarity index value of weed species in different crops under a specific area or among the area indicated that weed control measure should be adopted on crop basis in a specific area considering the dominant weed species. J. Bangladesh Agril. Univ. 15(2): 148-157, December 2017